X-inactivation patch size in human female tissue confounds the assessment of tumor clonality. - Novelli, M; Cossu, A; Oukrif, D; Quaglia, A; Lakhani, S; Poulsom, R; Sasieni, P; Carta, P; Contini, M; Pasca, A; Palmieri, G; Bodmer, W; et al. (2003)
Most models of tumorigenesis assume that tumors are monoclonal in origin. This conclusion is based largely on studies using X chromosome-linked markers in females. One important factor, often ignored in such studies, is the distribution of X-inactivated cells in tissues. Because lyonization occurs early in development, many of the progeny of a single embryonic stem cell are grouped together in the adult, forming patches. As polyclonality can be demonstrated only at the borders of X-inactivation patches, the patch size is crucial in determining the chance of demonstrating polyclonality and hence the number of tumors that need to be examined to exclude polyclonality. Previously studies using X-linked genes such as glucose-6-phosphate dehydrogenase have been handicapped by the need to destroy the tissues to study the haplotypes of glucose-6-phosphate dehydrogenase [Fialkow, P.-J. (1976) Biochim. Biophys. Acta 458, 283-321] or to determine the restriction fragment length polymorphisms of X chromosome-linked genes [Vogelstein, B., Fearon, E. R., Hamilton, S. R. and Feinberg, A. P. (1985) Science 227, 642-645]. Here we visualize X-inactivation patches in human females directly. Results show that the patch size is relatively large in both the human colon and breast, confounding assessment of tumor clonality with traditional X-inactivation studies.